Now it is winter - Spinelli, Eileen; DePalma, Mary Newell (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 2004)
A young mouse is encouraged by his mother to enjoy winter while waiting for spring to come.
Keywords: Mice -- Fiction; Winter -- Fiction